Committee Against Camarillo Airport "Quality Environment" Letter - Mary R. Gayle:::President, Committee Against Camarillo Airport::: (1972)
Letters from the Committee Against Camarillo Airport discussing the decision made by the City Council of Oxnard to apply jointly with Ventura County for the ownership of the former Oxnard Air Force Base.